STRATEGI AIPAC DALAM MENJAGA KEBERLANJUTAN BANTUAN LUAR NEGERI AMERIKA SERIKAT UNTUK ISRAEL TAHUN 2009-2013 - Priyatna, I Putu Yahya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
ABSTRACT Bilateral relations between United States and Israel are good because of the similarity of interest, ideology, and the full support of American Israel Public Affair Committee (AIPAC) which is a Jewish interest group that has a great power in influencing United States Policy. The aim of the research is to discuss AIPAC strategies in its efforts to prevent Israel from sequestration. The concept used is the interest group, lobby and foreign aid. The author collects the data from books, academic journal, mass media, and websites which is related to the influence of Jewish interest group in sequestration issues. AIPAC lobby implements various techniques to deal with the issues of sequestration, including Legislative Lobbying, Executive Lobbying, Electoral Lobbying, Grassroots of Indirect Lobbying. Keywords : Interest group, foreign aid, sequestration, lobby.